2018
DOI: 10.7754/clin.lab.2018.180331
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Antibiotic Resistance, Biofilm Formation and lasB Gene in Pseudomonas Aeruginosa Isolated from Burn Patients

Abstract: Background: Pseudomonas aeruginosa is a major cause of hospital-acquired infection due to its high antibiotic resistance and biofilm formation ability. P. aeruginosa produces elastase lasB during biofilm formation, which can influence properties of biofilm. This study was carried out to evaluate the antibiotic resistance and distribution of the lasB gene among biofilm-producing P. aeruginosa strains isolated from burn patients. Methods: A total of 128 clinical samples were collected from burn patients. The P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Regarding extracellular protease encoding lasB (elastase LasB) and aprA (alkaline protease AprA), lasB was detected in a higher rate (100.0%) than in clinical settings (Roshani-Asl et al 2018). Due to this exclusiveness, it was not possible to evaluate the previously reported relationship between the presence of lasB gene and biofilm-forming ability or Imipenem, Piperacillin/Tazobactam resistance (Roshani-Asl et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding extracellular protease encoding lasB (elastase LasB) and aprA (alkaline protease AprA), lasB was detected in a higher rate (100.0%) than in clinical settings (Roshani-Asl et al 2018). Due to this exclusiveness, it was not possible to evaluate the previously reported relationship between the presence of lasB gene and biofilm-forming ability or Imipenem, Piperacillin/Tazobactam resistance (Roshani-Asl et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding extracellular protease encoding lasB (elastase LasB) and aprA (alkaline protease AprA), lasB was detected in a higher rate (100.0%) than in clinical settings (Roshani-Asl et al 2018). Due to this exclusiveness, it was not possible to evaluate the previously reported relationship between the presence of lasB gene and biofilm-forming ability or Imipenem, Piperacillin/Tazobactam resistance (Roshani-Asl et al 2018). Regarding aprA, the previously reported clinical frequencies were 27.2% among patients with otitis media (Hassuna 2016), 28.6% among burned patients (Fazeli and Momtaz 2014) and 100% in intensive care units (ICUs) (Bradbury et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the destruction of pseudomonas biofilm by antimicrobial peptides is not dependent on the effect of lasB. The role of lasB in the biofilm formation process is still controversial [31][32][33]. Thirdly, only the hBD3-CBD-treated PA14 ΔexsA group showed a lower hcnA expression.…”
Section: Discussionmentioning
confidence: 98%
“…Such variation within species would make it unreliable to establish a concentrate relationship on the biofilm formation and genus. Moreover, significant correlation was found between antibiotic resistance and biofilm formation in Pseudomonas aeruginosa [45,46] while other studies have found otherwise [47]. A study between P. aeruginosa from environmental and human sources observed significantly weaker biofilm formation and susceptibility to most antibiotics from environmental isolates as compared to human sources [48].…”
Section: Discussionmentioning
confidence: 99%